Modernization Process at Palangki Livestock Market - Ismail Edfar (Universitas Negeri Medan, 2022)
This article aims to describe the factors that influence the modernization process that took place in the Palangki cattle market. The modernization process that takes place in the livestock market can be seen from the operational facilities, market management, and people. Data regarding this study were collected by field observations, in-depth interviews and literature studies, then analyzed using qualitative methods. This study came to the conclusion that the modernization that occurred in the Palangki cattle market not only affected the economic development of the market, but also affected the people living around the livestock market. There are several factors that cause modernization to take place in the Palangki livestock market including capital, people, and location. Capital is needed to carry out development. The second is humans who are the movers or managers of the livestock market. Third is location, strategic livestock market development will certainly affect market development, ease of access to livestock markets is something that must be taken into account before carrying out development. This paper is intended to describe how modernization occurs in the livestock market and the factors that influence it.Keywords: cattle market, palangki, modernization